Perbandingan Pola Pembelajaran Kontekstual dan Tahap Pemahaman Konsep Sains Pelajar Sekolah Menengah Rendah di Malaysia dan Singapura - Sun, Low Kee; Fah, Lay Yoon (Sains Humanika, 2013)
In order to produce world class human model, science education that is able to provide individuals who are innovative, creative and productive was the main focus of the education system in Malaysia. Malaysian student science performance deteriorating sharply against other Asian countries (TIMSS 2007) has resulted in our country is falling behind. Failure to relate the lesson content with real-life context of a major source of students are not interested and thus not able to capture the knowledge of good science. Contextual learning approach to build a concrete relationship between the content of science education in the context of the day has become the main approach outlined in the syllabus of Science in Malaysia and also in many countries. Thus contextual learning pattern also focus on the survey. This study examined the differences contextual learning pattern and level of understanding of science concepts junior high school students in Malaysia and Singapore. Data were collected from the Trends in International Mathematics Program and Science Study 2007 (TIMSS), the sample consisted of 4,466 students of Malaysia and 4,599 students of Singapore. The results showed that there were significant differences between the patterns of contextual learning and students' level of understanding of the concept of Sciences Malaysia and Singapore. Singapore students showed a higher level of understanding of Malaysian students in all domains, especially in the understanding and application domains. The results also showed a significant relationship between contextual learning pattern with students' understanding of Science concepts, but the regression of these two variables is very low.